Kajian Hukum Pidana Terhadap Tindak Pidana Penyalahgunaan Narkotika yang Dilakukan Anggota TNI Dihubungkan dengan Pasal 103 KUHP - Syahrial; Maya Intan Pratiwi; Rian Prayudi Saputra (PT PUSTAKA CENDEKIA GROUP, 2025)
The regulation of military criminal law is subject to the KUHPM and also to criminal laws outside the KUHPM, including Law No. 35 of 2009 on Narcotics. The KUHPM does not explicitly regulate narcotics abuse; therefore, military courts apply Article 2 of the KUHP, which applies to all offenders, whether civilian or military. The principle of lex specialis derogate legi generalis applies, meaning the Narcotics Law, as a special regulation, takes precedence over the KUHP. Principal penalties are imposed based on Article 10(a) of the KUHP and Article 6(a) of the KUHPM, while additional penalties such as dismissal refer to Article 26 of the KUHPM. This article is mutatis mutandis, meaning it can be applied by the judge without being proven as an element of the offense. Judges have discretion in determining sentences but must base their decisions on complete considerations. If such considerations are lacking, the Supreme Court may annul the verdict. Case analysis shows that judges place greater emphasis on juridical considerations based on trial facts and statutory provisions.